Análise de redes sociais: o método e sua utilização nas Ciências Sociais brasileiras - Ciro Antônio da Silva Resende (Ciências Sociais Unisinos)
This article analyzes descriptively the use of the method ofsocial network analysis in the main publications in the Brazilian Social Sciences, in order to offer contributions for two questions: (1) what is the social network analysis?; and (2) how often has the method been used in the main publications in this area? About the first question, extensive bibliographical research is undertaken. Regarding the second question, the publications, between 2006 and 2016, of the journals with the best ranking for the following areas are analyzed: (1) Anthropology and Archeology, (2) Political Science and International Affairs, and (3) Sociology. The analysis of this method's use indicates the existence of a small number of papers, and the absence ofsubstantial differences between thejournals of the three areas. However, the papers that were found exemplify the interdisciplinary aspect ofsocial network analysis and its capability to be combined with other techniques in the study of various phenomena.